Harry Potter and the Deathly Hallows. Part 1 [videorecording (DVD)] - Yates, David, 1963-; Radcliffe, Daniel, 1989-; Grint, Rupert, 1988-; Watson, Emma, 1990-; Bonham Carter, Helena, 1966-; Coltrane, Robbie; Davis, Warwick; Fiennes, Ralph; Gambon, Michael; Gleeson, Brendan; Griffiths, Richard, 1947-2013; Hurt, John, 1940-2017; et al. (Warner Home Video, 2011)
Part 1 begins as Harry, Ron and Hermione set out on their perilous mission to track down and destroy the secret to Voldemort's immortality and destruction--the Horcruxes. On their own, without the guidance of their professors or the protection of Professor Dumbledore, the three friends must now rely on one another more than ever. But there are Dark Forces in their midst that threaten to tear them apart. Harry's only hope is to find the Horcruxes before Voldemort finds him.